2020
DOI: 10.1080/2162402x.2020.1806009
|View full text |Cite
|
Sign up to set email alerts
|

Potential lung attack and lethality generated by EpCAM-specific CAR-T cells in immunocompetent mouse models

Abstract: The tumoricidal efficiency of human CART cells is generally evaluated using immune-deficient mouse models; however, due to their immune-incompetency and the species-specific reactivity of a target antigen, these models are problematic to imitate CART induced adverse effects in the clinic. Epithelial cell adhesion molecule (EpCAM) is a tumor-associated antigen overtly presented on the cell surface of various carcinomas, making it an attractive target for CART therapy. Here, we developed an anti-mouse EpCAM CAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…In this regard, CAR-T cells targeting epithelial cell adhesion molecule (EpCAM), a tumor-associated antigen overtly presented on the cell surface of various carcinomas, is a typical precedent. Although anti-human EpCAM CAR-T cells unable of recognizing mouse EpCAM eradicated established tumor xenografts without toxicities in the immunodeficient animal models, anti-mouse EpCAM CAR-T cells induced severe pulmonary immunopathology in theimmunocompetent mice due to CAR-T recognition of basal EpCAM expression in normal lung ( 49 ). In addition, we may learn from the experience of targeting ROR1 by CAR T cells as these two molecules have similar expression profiles in both normal and tumor tissues ( 10 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CAR-T cells targeting epithelial cell adhesion molecule (EpCAM), a tumor-associated antigen overtly presented on the cell surface of various carcinomas, is a typical precedent. Although anti-human EpCAM CAR-T cells unable of recognizing mouse EpCAM eradicated established tumor xenografts without toxicities in the immunodeficient animal models, anti-mouse EpCAM CAR-T cells induced severe pulmonary immunopathology in theimmunocompetent mice due to CAR-T recognition of basal EpCAM expression in normal lung ( 49 ). In addition, we may learn from the experience of targeting ROR1 by CAR T cells as these two molecules have similar expression profiles in both normal and tumor tissues ( 10 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also suggested that EpCAM can be utilized as a target antigen for CAR-T cell therapy, potentially selectively eliminating CTCs. However, their reported efficacy seems to also be accompanied by an unfavorable toxicity profile [157].…”
Section: Ctcs As a Therapeutic Targetmentioning
confidence: 99%
“…Then, tissues are stained with hematoxylin and eosin, and other antibodies to check for CAR-T cell infiltration and organ damages. [147]…”
Section: Safety Profiles Of Car-t Therapymentioning
confidence: 99%
“…For intra-tumoral T cell numbers, tumors are first sectioned and digested to determine the numbers of tumorinfiltrating lymphocytes via flow cytometry. [147]…”
Section: T Cell Proliferationmentioning
confidence: 99%